Meningkatkan Ekonomi Masyarakat saat Pandemik Covid-19 melalui Budidaya Ikan Lele dalam Ember di Desa Cibitung Tengah Tenjolaya Kabupaten Bogor - Sumardi Sumardi; Zulpahmi Zulpahmi; Abdul Latif (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
The Covid-19 pandemic had a negative impact, namely an increase in unemployment and poverty. This, based on a survey of unemployment and poverty. This, based on a survey of unemployment and poverty as a result of the Covid-19 pandemic conducted by the Indo Barometer Institute with the RRI’s Pustilbangdiklat, the unemployment rate increased after Covid-19 was 95,6%. Increasing the community's economy during the Covid-19 pandemic through the cultivation of catfish in buckets aims to help people play an active role in improving the family economy during the Covid-19 pandemic. Cultivating catfish in buckets can be used as an alternative for Central Cibitung, Tenjolaya, Bogor to improve the economy.